Association of TNF-α gene promoter region polymorphisms in bovine leukemia virus (BLV)-infected cattle with different proviral loads - Lendez, Pamela Anahi; Passucci, Juan Antonio; Poli, Mario Andres; Gutierrez, Silvina Elena; Dolcini, Guillermina Laura; Ceriani, Maria Carolina (2017)
Tumor necrosis factor alpha (TNF-α) is a pleiotropic cytokine involved in the immune response against viral and other infections. Its expression levels are affected by a polymorphism in the promoter region of the gene. Bovine leukemia virus is a retrovirus that infects cattle and develops two different infection profiles in the host. One profile is characterized by a high number of proviral copies integrated into the host genome and a strong immune response against the virus, while the most relevant property of the other profile is that the number of copies integrated into the host genome is almost undetectable and the immune response is very weak. We selected a population of cattle sufficiently large for statistical analysis and classified them according to whether they had a high or low proviral load (HPL or LPL). Polymorphisms in the promoter region were identified by PCR-RFLP. The results indicated that, in the HPL group, the three possible genotypes were normally distributed and that, in the LPL group, there was a significant association between the proviral load and a low frequency of the G/G genotype at position -824.